Relationship among maximal grip, throwing velocity and anthropometric parameters in elite water polo players - Ferragut, C.; Vila, H.; Abraldes, J. A.; Argudo, F.; Rodriguez, N.; Alcaraz, P. E. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: As independent aspects, body size, body composition, and physiological performance of elite athletes have aroused the interest of sports scientists but, unfortunately, studies that combine these aspects are scarcely avalaible in water polo. The aim of the present study was to: 1) to develop an anthropometric profile of highly skilled male Water Polo players, and 2) to identify significant relationships between these features and overhead throwing velocity in highly skilled male water polo players. METHODS: Thirteen male water polo players, with a mean age of 26.10±4.82, were recruited from the Spanish Water Polo team and an anthropometric assessment on all of them was carried out. Throwing velocity was evaluated in three different situations from the 5 m-penalty line on the center of the water polo goal: A) throwing without a defender nor a goalkeeper; B) throwing with a goalkeeper only, and C) 3) armfuls running shot with goalkeeper. Maximal handgrip was also tested. RESULTS: Biacromial breadth shows a significative correlation with hand grip in water polo players (r=0.792; P=0.001) and also correlates with Throwing velocity (r=0.716; P<0.001). Biepicondylar femur breadth correlates significatively with hand grip (r=0.727; P<0.05) and also with throwing velocity in "throwing with goalkeeper" situation (r=0.664; P<0.05). Hand grip shows a significant correlation with throwing velocity in "throwing with goalkeeper" situation (r=0.603; P<0.05). CONCLUSION: In conclusion, body mass aspects are not related with throwing velocity in highly skilled Water Polo players. Maximal hand grip is related with throwing velocity in "throwing with goalkeeper" situation. More investigations about water polo are necessary.